Olfactory threshold values of C4VOE as test agents for measuring the olfactory capability - Sukardjo, Sukardjo (Universitas Gadjah Mada, 1994)
The preliminary clinical study on seven volatile agents and their olfactory threshold values of cadinum, camphora, capsaicin, carbon disulphide, vanilla, oleum menthae piperitae and ether has been performed. Their concentrations in solution and as a vapour could be measured by regression calculation. The olfactory detection threshold of these evaporated agents constituted the following concentrations: cadinum 0.12325/0.007968, camphora 0.01993/0.0045364, capsaicin 0.0118/0.0007573, carbon disulphide 0.02703/0.0066363, vanilla 0.01884/0.004255, oleum menthae piperitae 0.01228/0.002064, and ether 0.014801/0.0003613. These agents could be normally recognized by healthy volunteers.The concentration of the agents can be drawn and displayed in linear graphic by arithmetic logarithm with 30% different vapour concentration for each agent. These volatile agents as test materials, based on these findings were called